The Effect Of Increasing Generation Z Debt Seen From Financial Attitudes, Financial Literacy, Locus Of Control On Financial Management Behavior: In The City Of Bandung - Rachman, Enda Ananda Azulfa; Dewi, Andrieta Shintia (JAF (Journal of Accounting and Finance), 2024)
The current rapid economic changes, especially in the financial sector of Generation Z, are very easily influenced by the development of the times which has an impact on their financial management behavior. Decisions on consumptive behavior can be influenced by various factors that have a significant impact on their financial, emotional, and social lives. Financial management behavior is the most important factor for every individual in managing daily finances. In this study, the author will examine the influence of financial attitudes, financial literacy, and locus of control on financial management behavior in generation Z of Bandung City. A sample size of 400 generation Z in the city of Bandung has been included for this study. This study is a quantitative research by distributing questionnaires and using multiple linear regression methods, as well as non-probability sampling with purposive sampling techniques using SPSS ver 25. It was found from the findings of the research that financial attitudes, financial literacy, and locus of control have a positive and significant influence on financial management behavior.Keyword: Financial Attitude; Financial Literac;, Locus of Control; Financial Managamenet Behavior.